The Effect of Colon Targeted Delivery of Celecoxib Loaded Microspheres on Experimental Colitis Induced by Acetic Acid in Rats - Madhusudhan, Alle (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The aim of the present study is to develop colon targeted drug delivery of chitosan microspheres with celecoxib as a model drug. Materials and Methods: Mucoadhesive microspheres were prepared using chitosan as a core polymer and coated with Eudragit S-100 by a solvent evaporation technique. The effect of different microsphere formulations was studied. Results: In vitro release study, core microspheres are found to show burst release in the first 1 h, whereas coated microspheres exhibit a controlled release, and thus suitable for colon target drug delivery. Through an in vivo study, we investigated the effect of the coated microspheres in rats exposed to experimental colitis. Colitis was induced in rats by rectal instillation of acetic acid. Rats experienced hemorrhagic diarrheic, body weight loss, rise in myeloperoxidase (MPO), and reduction of reduced glutathione (r-GSH) activity by cyclooxygenase (COX), after 5 days administration of acetic acid. Oral administration of coated microspheres (5 mg/kg) twice-a-day to rats after induction of colitis significantly attenuated the severity of the colonic injury. In addition, there was a significant reduction of MPO and COX levels but arises in the levels of GSH. Conclusion: Thus, the study provided the evidence that coated microspheres are beneficial in the treatment of inflammatory bowel disease with minimal side effects.